THU0666 Patient global assessment is more sensitive to change than health-related quality of life instruments in early axial spondyloarthritis over 3 years: data from the desir cohort. (15th June 2017) - Puyraimond-Zemmour, D; Desthieux, C; Ruyssen-Witrand, A; Fautrel, B; Gossec, L
Abstract : Background: Several questionnaires assess similar constructs of global patient-reported state or Health-Related Quality of Life (HRQoL). Objectives: To evaluate sensitivity to change (ie, discriminance) of several questionnaires in early axial spondyloarthritis (axSpA) over 3 years of follow up: the SF36, axial spondyloarthritis quality of life (ASQoL), axial spondyloarthritis health assessment questionnaire (AS-HAQ) and patient global assessment (PGA). Methods: DESIR is an ongoing prospective, multicenter, longitudinal, observational French cohort (1). Patients had inflammatory back pain of more than 3 months and less than 3 years suggestive of axSpA. For our analysis, only patients with no missing data for MCS and PCS SF36 values during the first 3 years were included. A global construct of patient global state was assessed by the SF36 questionnaire and its 2 subscales (scored 0–100 with higher scores indicating better status): the physical composite score (PCS) and the mental composite score (MCS), AsQoL, a disease-specific HRQoL scale, PGA and AS-HAQ. ASDAS-CRP was used as comparator. Each outcome was assessed at baseline, 6 months, 12 months, 24 months and 36 months. Standardized mean differences (SMD) were calculated using Cohen's effect size with confidence intervals, between each time point for each outcome. A SMD <0.5 is usually considered small, between 0.5 and 0.8 moderate and >0.8 as important. Results: In all, 442 patients were analyzed: at baseline, mean age was 34.2±8.6 years; mean disease duration was 18.6±10.7 months; 239 (54%) were females, 274 (62%) had HLAB27 and 124 (28%) had radiological sacroiliitis. At baseline, patients were not in an optimal state; improvement was clear up to month 6 then minimal (at the group level): Table. Sensitivity to change was greatest for PGA, then ASQoL whereas AS-HAQ, MCS and PCS appeared the least discriminant measure (Table). Conclusions: PGA was more sensitive to change than HRQoL measures in early axSpA. ASDAS appeared also sensitive to change. Changes in all the measures were very small at the group level after 6 months of follow-up indicating the concepts convered may be as much patient- as disease-related. References: Dougados M. et al. Clinical presentation of patients suffering from recent onset chronic inflammatory back pain suggestive of spondyloarthritis: The DESIR cohort.Joint Bone Spine. 2015;82(5):345–51. Disclosure of Interest: None declared